QA-Frame as Media in Learning “Selling and Buying” E xpressions of Traders in Kawasan Wisata Kota Lama Semarang - Dian Puji Lestari; Rizza Fijriatur Rohmah; Ulfiana Koerunisa (ETERNAL (English Teaching Journal), 2018)
The background of this research is based on phenomenon that traders’ of Kawasan Wisata Kota Lama Semarang in speaking needs to be improved. Some of them were still lazy to speak English because they do not have enough idea of what to speak. QA-Frame is a speaking learning media that contains selling and buying expressions with the meaning. The purpose of this research can be stated as follow: (1) To find out how is the implementation of QA-Frame as learning media for traders in Kawasan Wisata Kota Lama Semarang. (2) To find out what are the problems faced by traders through QA-Frame as media in Kawasan Wisata Kota Lama Semarang.This research is qualitative method. The subject of this research was traders in Kawasan Wisata Kota Lama Semarang. The researchers took three traders for our sample. They are Mr. Nanang; Mr. Riki; and Mrs. Desi. They were traders in Pasar Klitikan. In collecting the data, the researchers used observation and interview. The result of this research showed thatthe implementation of QA-Frame media accepted for the traders to improve their selling and buying expression. In the other hand, the implementation of QA-Frame media have some problems, such as: possessed limited English speaking skill, the traders only knew some basic vocabulary about the price, the small traders did not “have the necessary vocabulary to give directions to tourists”, the traders cant not memorization and repetition, production and communicationstrategies to process the language input from various sources for their spoken output, the traders have limited  grammatical, sociolinguistic and discourse competence.